IMPLEMENTASI ASUHAN KEBIDANAN BERKELANJUTAN (CONTINUITY OF CARE) DI TPMB J PASAR MINGGU JAKARTA SELATAN TAHUN 2023 - Yustisia, Cahya (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2023)
Continuity of care (COC) is a comprehensive and continuous activity starting from the period of pregnancy, birth, postpartum, newborn and family planning (KB) which is needed by every woman. Continuty of care is carried out by health workers (midwives) who have the aim of improving comprehensive and sustainable services. This study aims to analyze the results of implementing sustainable and complementary midwifery care at TPMB J. This case study used the research method in the form of midwifery care given to one respondent who was 34 years old, the study started from the third trimester with 37 weeks of gestation until 42 days postpartum. This study used complementary care interventions in the form of pregnancy exercise, birth ball, oxytocin massage, breast care, and baby massage. The results of this case study show that care has been provided in accordance with midwifery care standards. It is hoped that all midwives can carry out midwifery care on an ongoing basis.